Serine Metabolism Supports the Methionine Cycle and DNA/RNA Methylation through De Novo ATP Synthesis in Cancer Cells - Maddocks, Oliver D.K. (Mol Cell, 2016)
Crosstalk between cellular metabolism and the epigenome regulates epigenetic and metabolic homeostasis and normal cell behavior. Changes in cancer cell metabolism can directly impact epigenetic regulation and promote transformation. Here we analyzed the contribution of methionine and serine metabolism to methylation of DNA and RNA. Serine can contribute to this pathway by providing one-carbon units to regenerate methionine from homocysteine. While we observed this contribution under methionine-depleted conditions, unexpectedly, we found that serine supported the methionine cycle in the presence and absence of methionine through de novo ATP synthesis. Serine starvation increased the methionine/S-adenosyl methionine ratio, decreasing the transfer of methyl groups to DNA and RNA. While serine starvation dramatically decreased ATP levels, this was accompanied by lower AMP and did not activate AMPK. This work highlights the difference between ATP turnover and new ATP synthesis and defines a vital function of nucleotide synthesis beyond making nucleic acids.